Systems Approach To Evaluate Growth And Meat Production Of Sheep Under Two Production Systems - Wattanachant, Chaiyawan (1999)

(untitled)
The growth and carcass performance of sheep reared under integration in the mature oil palm plantation and feedlot system were studied using a systems approach. Simulation models of the growth and carcass of the Dorset x Siamese Long Tail (DSLT) and Dorset x Malin (DMalin) sheep were described. To construct simulation models to evaluate a production system, a series of studies were carried out. Firstly, the dry matter intake, energy intake and energy requirements of sheep were determined. Secondly, the live weight changes, carcass, muscle, fat and bone weight changes were measured. Thirdly, the models were constructed to describe the growth and carcass performance of sheep under the two production systems. Validations of the simulation models were done by comparing the simulated data with the actual data of live weight, carcass and its tissue weight.